Dialogues d’époux sur les stèles funéraires attiques - Élise Pampanay (Frontière·s)
Most of the iconography and inscriptions of the Classical Attic tombstones are conventional when honoring the dead. However, in some cases, studying the relationships between the figured relief and the inscription shows that the monuments are designed in an unconventional way, while seeking to establish a lost connection, particularly between husbands and wives. The sema is precisely a medium between the living and the dead, whether the living be close relatives or passers-by confronted to this memorial. Indeed, a third person can play a part in crossing this threshold between the living and the dead in this imaginary device of communication. The passer-by is invited, by the image or the text, to observe these forever still faces and to read aloud what the epigram has to say in order to give a new breath to the missing voices. There are several types of dialogue, first between visual elements of the stela, then between the iconography and the inscription. It is also crucial to study the way the speaker addresses the dead relative. Three case studies of visual and textual dialogues between husbands and wives are particularly interesting in that respect.